2017
DOI: 10.1159/000455397
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive, Individualized, Person-Centered Management of Community-Residing Persons with Moderate-to-Severe Alzheimer Disease: A Randomized Controlled Trial

Abstract: Background/Aims: The aim was to examine added benefits of a Comprehensive, Individualized, Person-Centered Management (CI-PCM) program to memantine treatment. Methods: This was a 28-week, clinician-blinded, randomized, controlled, parallel-group study, with a similar study population, similar eligibility criteria, and a similar design to the memantine pivotal trial of Reisberg et al. [N Engl J Med 2003;348:1333-1341]. Twenty eligible community-residing Alzheimer disease (AD) subject-caregiver dyads were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…We identified three studies evaluating specialist palliative care services 1921 and five evaluating non-specialist palliative care interventions (Table 2). 2227 One study on non-specialist palliative care intervention was reported in two articles. 22,23 Four of the studies presented evidence from the United States, 19,20,24,25 two from Italy, 22,23,27 and one each from the United Kingdom 26 and Japan.…”
Section: Resultsmentioning
confidence: 99%
“…We identified three studies evaluating specialist palliative care services 1921 and five evaluating non-specialist palliative care interventions (Table 2). 2227 One study on non-specialist palliative care intervention was reported in two articles. 22,23 Four of the studies presented evidence from the United States, 19,20,24,25 two from Italy, 22,23,27 and one each from the United Kingdom 26 and Japan.…”
Section: Resultsmentioning
confidence: 99%
“…Other research likewise emphasizes benefits accruing from arts-based programming for persons in the middle to late stages of dementia (Young, Camic, & Tischler, 2015;Humphrey et al, 2019). Both the Olazarán et al (2010) and Reisberg et al (2017) studies confirm the efficacy of including person-centered programming in the treatment of persons across the multiple stages of ADRD. Over the past 20 years, there has been a steady shift from seeing dementia and those who "suffer" from it solely as a disease entity to be treated medically, to a chronic, progressive condition that benefits from interventions that build on an individual's capacity to learn and foster good quality of life.…”
Section: Evolving Perspectives On Adrd: From Disease-focused To Persomentioning
confidence: 81%
“…A more recent randomized controlled trial (Reisberg et al, 2017) examined the added benefits of a comprehensive, individualized, person centered management program (CI-PCM) in combination with a commonly prescribed to drug treatment of memantine for individuals with moderate-to-severe Alzheimer's Disease. The comprehensive, individualized, person centered management program was based on thirteen principles, which included, for example, (#6) treating persons with Alzheimer's Disease with dignity and respect as a person, not as an object, (#7) learning the Alzheimer's Disease person's history, individual tastes and preferences, talents, shortcomings, and personal needs, (#9) establishing a healthy, supportive, structured and flexible routine with daily fun scheduled in the routine, and (#10) using Memory Coaching to teach the Alzheimer's Disease person new skills, or skills they may have forgotten, helping to rebuild the Alzheimer's Disease person's self-esteem and self-respect (Reisberg et al, 2017, pp.…”
Section: Evolving Perspectives On Adrd: From Disease-focused To Persomentioning
confidence: 99%
“…These drugs have modest symptomatic effects but do not have profound disease‐modifying effects [1]. Attempts to treat amyloid toxicity are underway by a number of groups [2,3], as are a variety of other approaches [4]. A complete review of current AD therapies can be found in a 2018 publication in this journal [5].…”
Section: Introductionmentioning
confidence: 99%